THE PERFORMANCE OF EMPLOYEES ANALYSIS IN STRUCTURAL EQUATION MODELLING TO CONSTRUCT THE ON SHIP SCOUNTING SERVICE - Yohanes Susanto; Sardiyo Sardiyo (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2023)
This study aims to analyze the effect of the quality of human resources and organizational structure on employee performance with work motivation as an intervening variable. The research sample is a scouting service company for river and sea transportation vessels located in urban rivers to the sea estuary in the city of Palembang, Indonesia, PT. Hexa Fortuna at Breech Marine. as service executor. Respondents of ship employees were 54 respondents. The research model analysis method uses Partial Least Square (PLS) with SMART PLS 3.0 software. The results obtained in the first sub-structure that the quality of human resources and organizational structure partially have a positive and significant effect on work motivation. However, the organizational structure has a more dominant influence. In the second sub structure, the quality of human resources, organizational structure and work motivation partially affect employee performance. organizational structure has a more dominant influence. The indirect effect between the quality of human resources and organizational structure on employee performance mediated by work motivation shows significant results. This shows that the work motivation variable is very influential in mediating the two variables.